Pengembangan Program Pembelajaran Kewirausahaan Untuk Generasi Mu - Ernawati; Nanda, Agustia; Nurul Ain Alifah Abu Bakar; Nurannisa; Muh. Fajrin; Andi Muhammad Naufal Nuzurkam (akultas Ilmu Sosial dan Ilmu Politik, 2024)
Abstract Entrepreneurship development has become the main focus in the education of the younger generation to improve entrepreneurial skills and economic independence. This journal discusses approaches and implementation in developing entrepreneurship learning programs for the younger generation. The research methods used include literature reviews, case studies, and qualitative and quantitative analysis of existing programs. This study identifies several key approaches in developing entrepreneurship learning programs, including the integration of entrepreneurship curricula in the formal education system, practical skills training, and the use of technology and innovation in the learning process. The implementation of these programs shows varying results, but in general provides a positive contribution to the development of entrepreneurial attitudes and business skills in the younger generation. Keywords: Entrepreneur, Economic, Indpendence Abstrak Pengembangan kewirausahaan telah menjadi fokus utama dalam pendidikan generasi muda untuk meningkatkan keterampilan berwirausaha dan kemandirian ekonomi. Jurnal ini membahas pendekatan dan implementasi dalam pengembangan program pembelajaran kewirausahaan untuk generasi muda. Metode penelitian yang digunakan meliputi tinjauan pustaka, studi kasus, serta analisis kualitatif dan kuantitatif terhadap program - program yang ada. Studi ini mengidentifikasi beberapa pendekatan kunci dalam pengembangan program pembelajaran kewirausahaan, termasuk integrasi kurikulum kewirausahaan dalam sistem pendidikan formal, pelatihan keterampilan praktis, serta pemanfaatan teknologi dan inovasi dalam proses pembelajaran. Implementasi program -program ini memperlihatkan hasil yang bervariasi, tetapi secara umum memberikan kontribusi positif terhadap pengembangan sikap wirausaha dan kemampuan bisnis pada generasi muda. Kata Kunci: Wirausaha; Ekonomi; Mandiri